2017
DOI: 10.1364/ao.56.003142
|View full text |Cite
|
Sign up to set email alerts
|

Superlensing microscope objective lens

Abstract: Abstract:Conventional microscope objective lenses are diffraction limited, which means that they cannot resolve features smaller than half the illumination wavelength. Under white light illumination, such resolution limit is about 250-300 nm for an ordinary microscope. In this paper, we demonstrate a new superlensing objective lens which has a resolution of about 100 nm, offering at least two times resolution improvement over conventional objectives. This is achieved by integrating a conventional microscope ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Our previous work presented in 2017 provided a simple but efficient approach to adopt microsphere lens in an ordinary microscope. With a 3D printed objective adaptor, the microsphere can work synchronously under objective to realize largearea scanning imaging [24]. Similar work was also demonstrated from H. Yang's previous paper [25].…”
Section: Introductionsupporting
confidence: 62%
“…Our previous work presented in 2017 provided a simple but efficient approach to adopt microsphere lens in an ordinary microscope. With a 3D printed objective adaptor, the microsphere can work synchronously under objective to realize largearea scanning imaging [24]. Similar work was also demonstrated from H. Yang's previous paper [25].…”
Section: Introductionsupporting
confidence: 62%
“…These processes are interlinked and coupled and complete model is still missing today. Most existing theoretical studies are based one or two processes above, leading to incomplete conclusions and debates [22,33,31,34,35,18,36,24,37,38,19,[39][40][41].…”
Section: Microsphere and Microcylindermentioning
confidence: 99%
“…Subsequently, the research focus shifted towards applications 17 26 , but in these papers super-resolution was achieved typically over a very small area that was comparable to the size of the used micro-object. Recently, it was demonstrated that the super-resolved area can be extended by various scanning methods 27 – 31 , including the super-resolution imaging ability of dielectric microspheres that were used in an atomic force microscopy (AFM) setup 32 , 33 . This technique extended the field-of-view of the imaging system, but also carried the drawbacks of an AFM system, namely the extreme sensitivity on vibration, requiring a dedicated setup.…”
Section: Introductionmentioning
confidence: 99%